Y"+4y=tg(2x)
Let us solve the differential equation "y''+4y=\\tg(2x)." The characteristic equation "k^2+4=0" of the homogeneous differential equation has the solutions "k_1=2i,k_2=-2i." The solution of the homogeneous equation is "y=C_1\\cos 2x+C_2\\sin 2x." Let us use the method of variation of parameters. We will find the solution of the differential equation in the form: "y=C_1(x)\\cos 2x+C_2(x)\\sin 2x." For this we should to solve the following system:
"\\begin{cases}C_1'(x)\\cos 2x+C_2'(x)\\sin 2x=0\\\\-2C_1'(x)\\sin 2x+2C_2'(x)\\cos 2x=\\tg 2x\\end{cases}"
"\\begin{cases}C_1'(x)=-C_2'(x)\\tg 2x\\\\2C_2'(x)\\tg 2x\\sin 2x+2C_2'(x)\\cos 2x=\\tg 2x\\end{cases}"
"\\begin{cases}C_1'(x)=-C_2'(x)\\tg 2x\\\\2C_2'(x)(\\frac{\\sin^2 2x}{\\cos 2x}+\\cos 2x)=\\tg 2x\\end{cases}"
"\\begin{cases}C_1'(x)=-C_2'(x)\\tg 2x\\\\2C_2'(x)(\\frac{\\sin^2 2x+\\cos^22x}{\\cos 2x})=\\tg 2x\\end{cases}"
"\\begin{cases}C_1'(x)=-C_2'(x)\\tg 2x\\\\2C_2'(x)(\\frac{1}{\\cos 2x})=\\tg 2x\\end{cases}"
"\\begin{cases}C_1'(x)=-C_2'(x)\\tg 2x\\\\C_2'(x)=\\frac{1}{2}\\sin 2x\\end{cases}"
"\\begin{cases}C_1'(x)=-\\frac{1}{2}\\frac{\\sin^2 2x}{\\cos 2x}\\\\C_2'(x)=\\frac{1}{2}\\sin 2x\\end{cases}"
It follows that "C_2(x)=-\\frac{1}{4}\\cos 2x+C_2" and "C_1(x)=-\\frac{1}{2}\\int\\frac{\\sin^2 2x}{\\cos 2x}dx=-\\frac{1}{4}\\int\\frac{\\sin^2 2x}{\\cos^2 2x}d(\\sin 2x)\n=\\frac{1}{4}\\int\\frac{\\sin^2 2x-1+1}{\\sin^2 2x-1}d(\\sin 2x)=\n\\frac{1}{4}\\int d(\\sin 2x)+\\frac{1}{4}\\int\\frac{1}{\\sin^2 2x-1}d(\\sin 2x)=\n\\frac{1}{4}\\sin 2x+\\frac{1}{8}\\int(\\frac{1}{\\sin2x-1}-\\frac{1}{\\sin2x+1})d(\\sin 2x)=\n\\frac{1}{4}\\sin 2x+\\frac{1}{8}(\\ln|\\sin2x-1|-\\ln|\\sin2x+1|)+C_1=\n\\frac{1}{4}\\sin 2x+\\frac{1}{8}\\ln|\\frac{\\sin2x-1}{\\sin2x+1}|+C_1"
We conclude that the general solution is
"y=(\\frac{1}{4}\\sin 2x+\\frac{1}{8}\\ln|\\frac{\\sin2x-1}{\\sin2x+1}|+C_1)\\cos 2x+(-\\frac{1}{4}\\cos 2x+C_2)\\sin 2x."
Comments
Leave a comment